Pengaruh Kualitas Produk, Sosial Media, dan Citra Merek terhadap Keputusan Pembelian pada Produk Somethinc - Sofy Cahyaningrum; Darwin Raja Unggul Saragih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: The skincare industry in Indonesia has experienced significant growth in recent years. This development is marked by the emergence of various local brands that actively compete to capture the domestic market, one of which is Somethinc. This brand has successfully gained consumer attention through product innovation, digital marketing strategies, and brand image reinforcement. This study aims to analyze the extent to which product quality, social media, and brand image influence consumers' purchasing decisions. A quantitative approach was employed using a survey method as the data collection tool. The sample consisted of 90 respondents selected through purposive sampling, with the criteria being consumers who had purchased Somethinc products through digital platforms. The data were analyzed using IBM SPSS version 25. The results show that product quality, social media, and brand image have a positive and significant influence on purchasing decisions. These findings indicate that consumers tend to consider product quality, engagement through social media, and brand perception before making purchasing decisions for skincare products.